Unexpected mitotype diversity of Simplimorpha promissa (Lepidoptera: Nepticulidae) in Ukraine and Armenia revealing a possible cryptic taxon - Orlovskytė, Svetlana; Dobrynina, Viktorija; Stonis, Jonas R. (Zootaxa, 2023)
In this paper, the results of a recent molecular study of the Cotinus-feeding, leaf-mining Simplimorpha promissa (Staudinger) (Lepidoptera: Nepticulidae) are discussed for the first time on the basis of samples collected in Ukraine and Armenia. Newly obtained mtDNA CO1-5’ sequences from these countries were compared with previously known sequences from France, Italy, Croatia and Greece. A mitotype network and a Neighbor-Joining tree of twenty-two specimens of S. promissa are provided. They show that the studied specimens from Ukraine and the rest of the European countries are genetically closer to each other than to the examined specimens from Armenia, thereby suggesting the Armenian specimens could represent a sister taxon to the European S. promissa. The study also revealed a significantly large genetic diversity of S. promissa in Ukraine.